Comparison and study of the preparation methods for phosphor layer in nuclear battery. (20th May 2020) - Jiang, Tongxin; Xu, Zhiheng; Tang, Xiaobin; Yuan, Zicheng; Wang, Hongyu; Bian, Mingxin
Summary: This work investigated the preparation and optimization of phosphor layer for radioluminescent nuclear battery, and analyzed the property change of the phosphor after irradiation. ZnS:(Cu, Al) with grain size of 5 μm was selected as the phosphor material, and AlGaInP semiconductor was used as the photovoltaic unit. Monte Carlo modeling was used to simulate energy deposition, absorbed dose, penetration of β particles in the phosphor. The optimized coupling scheme of radioisotope sources and phosphor layer was obtained based on comparison particle penetration depth and the output power of radioluminescent nuclear battery. The phosphor layer with 60 Co γ‐radiation enhanced the luminescence property up to 50% at the radiation dose of 871 kGy, which is considered as an optimized method of phosphor layer preparation. The radiation of 10 MeV electron was conducted to study the degradation based on the microscopic lattice characteristics, morphological changes, optical and electrical properties. Phosphors have excellent radiation resistance. The output power of nuclear batteries has only declined by 43% even when electron radiation dose reaches 8.56 MGy. The prospect for utilizing ZnS:(Cu, Al) phosphor as radiant energy conversion materials in nuclear battery was also discussed. Results provided an effective guideline for predict the service conditions of radioluminescent nuclear battery. Abstract : This work focused on the preparation and optimization of phosphor layer, which was used for energy conversion in radioluminescent nuclear battery. The study analyzed the electron irradiation effect of the phosphor. The prospect for utilizing such phosphor as intermediate materials in radioluminescent nuclear battery was also discussed.